Social responsibility and its relationship with Some Variables among students of Sultan Qaboos University - Sultanate of Oman - Al-Abri, Mohammed Nasser Ali (Journal of Educational and Psychological Sciences, 2022)
The aim of this study was to measure the level of social responsibility among students of Sultan Qaboos University in Sultanate of Oman in light of some variables (gender, birth order, family income level and Academic achievement). To achieve the aim of the study, the researcher used the descriptive correlative method and he used the social responsibility scale, which consists of (32) paragraphs divided into four dimensions: (Personal self-responsibility, Moral religious responsibility, Social responsibility and National responsibility). Its validity and steadfastness have been verified. A random sample was selected from the study population represented by the students in Sultan Qaboos University in Sultanate of Oman, 16359 male and female students enrolled in the academic year 2020-2021 according to the Deanship of Admission and Registration at the university. The sample consisted of (317) male and female students i.e. (2%) of the size of the study population. The results of the study concluded in the following:- The level of social responsibility was high in the study sample.- There were statistically significant differences at the level of significance (α≤0.05) in the estimations of the study sample on the level of social responsibility attributed to gender variable in favor of females.- There were no statistically significant differences at the level of significance (0.05≥α) in the estimations of the study sample on the level of social responsibility attributed to the variable of birth order.- There were no statistically significant differences at the level of significance (0.05≥α) in the estimations of the study sample on the level of social responsibility attributed to the variable of family income level.- There is a positive correlation and a statistical function between the social responsibility and Academic achievement.The research came out with the following recommendations:- Attention to the development of social skills that are related to the social responsibility of students at all levels, especially in adolescence, in a developmental, preventive, and curative manner.- Paying attention to specialized guidance programs in the field of social responsibility development at the community level, whether in the media, mosques, families, clubs and youth forums.- Carrying out studies similar to the current study, but with more comprehensive and broader samples.- Carrying out longitudinal studies to find out the impact of collective counseling programs for the development of social responsibility.
Keywords: Social Responsibility; Sultan Qaboos University; Birth Order; Academic achievement